Tropical origin for the impacts of the Atlantic Multidecadal Variability on the Euro-Atlantic climate - Davini, Paolo; von Hardenberg, Jost; Corti, Susanna (Environmental Research Letters, 2015)
Atlantic Multidecadal Variability (AMV) is known for influencing the mid-latitude climate variability, especially over the European region. This letter assesses the impact of the wintertime AMV in a group of 200-year atmospheric-only numerical experiments, in which the atmosphere is forced with positive and negative AMV-like sea surface temperatures (SSTs) and sea ice concentration patterns. Anomalies are applied separately to the whole North Atlantic ocean, to the extratropics (north of 30 degrees N) and to the tropics (between 0 degrees and 30 degrees N). Results show that AMV anomalies considerably affect the North Atlantic Oscillation (NAO), the jet stream variability and the frequency of atmospheric blocking over the Euro-Atlantic sector, resulting in a negative (positive) NAO during positive (negative) AMV. It is found that the bulk of the signal is originated in the tropics and it is associated with a Gill-like response - an anomalous upper tropospheric streamfunction dipole over the tropical Atlantic driven by the SST anomalies-and with the subsequent structural change of the upper-tropospheric jet, which affects the propagation of Rossby waves in the North Atlantic. Conversely, the NAO response is almost negligible when the AMV anomalies are applied only to the extratropics, suggesting that the relevance of SST anomalies along the North Atlantic frontal zone may be overestimated.